Vulneración del derecho a la defensa, en el trámite administrativo de la junta cantonal de protección de derechos del cantón Riobamba - Yuqui Hernández, Jenny Lilian (2023)
ABSTRACT Ecuador with the Constitution of the Republic that was created in 2008 is characterized mainly by the change within the legal system, the denomination of a State that guarantees rights and social justice implies unrestricted respect for the dignity of people at all times, with the so-called block of constitutionality that governs in our country, it is essential that the principles, rights and guarantees recognized explicitly and implicitly in the Ecuadorian legal system be respected. Within this neo-constitutionalism, the right to due process is recognized in article 76, it recognizes that, in any criminal, constitutional, administrative or any kind of process, it must be governed by this basic guarantee that includes the possibility of defending oneself and incorporating everything that is created assisted to prove his state of innocence. The Cantonal Board for the Protection of Rights, is an organization whose purpose is to safeguard the defense, protection and enforceability of the rights of children, adolescents, women victims of violence and older adults, through which an administrative process is carried out when there is a violation of them, however, it must be done subject to the right to due process. In the present research work, the inductive-deductive method was used, which served to study from a general context to a particular one, as well as the historical method that allowed an analysis of the creation of the Cantonal Board for the Protection of Rights of the Riobamba Canton and of the right to defense that is described in our norm supra, finally the synthetic analytical method was applied that allowed a detailed study to be carried out on an administrative resolution of the Cantonal Board for the Protection of Rights of the Riobamba Canton, where the violation of the right to defense Keywords: Constitution, Law to Prevent and Eradicate Violence Against Women, Regulation of the Law to Prevent and Eradicate Violence Against Women; Public Ordinances, Principles - Constitutional Guarantees.